Beyond formal compliance: Evaluation of the whistleblowing system implementation at PT XYZ - El Firdausy, Wildan; Adhariani, Desi; Budiman, Rachman Untung; Hendiyanto, Arman; Tanzil, Helen Riyani (Journal of Contemporary Accounting, 2026)
This study aims to evaluate the implementation of the Whistleblowing System (WBS) at PT XYZ by comparing the company’s disclosed WBS policies with the Whistleblowing System Guidelines issued by the National Committee on Governance Policy (Komite Nasional Kebijakan Governance [KNKG]) and by examining the alignment between the company’s stated policies and their actual implementation within its organizational environment and daily operations. Employing a qualitative descriptive approach, data was collected through interviews, observations, and documentation. The findings indicate that, in general, PT XYZ’s WBS policies conform to the KNKG guidelines. However, two key elements—continuous education and training and incentive mechanisms for whistleblowers—have not yet been implemented. The Human Capital and Internal Audit Departments explained that ongoing training and socialization activities have been conducted through programs on corporate culture and values, which they believe implicitly cover WBS principles. In contrast, employees outside the main departments responsible for WBS emphasized that dedicated and periodic training on whistleblowing procedures, separate from cultural orientation programs, is necessary. Moreover, several employees expressed the need for an additional reporting channel in the form of a dedicated and user-friendly digital application to enhance accessibility and confidentiality in reporting.